Myoepithelial carcinoma arising in recurrent pleomorphic adenoma of upper lip - Nitish Virmani; J P Dabholkar (Journal of Head & Neck Physicians and Surgeons, 2015)
Different patterns of malignant change may occur in pleomorphic adenoma; carcinoma ex-pleomorphic adenoma is one such malignant entity.Although in most instances, the features of malignant transformation are evident, some very well-differentiated cancers such as myoepithelial carcinoma or cancers that exhibit morphologically limited nuclear atypia may be somewhat challenging to diagnose. A 45 year old man presents to us with a recurrent swelling over the upper lip for ten years. It had been excised twice during this period; the histopathology being consistent with pleomorphic adenoma. This time, however, there was a co-existent ipsilateral submandibular swelling. He underwent wide local excision of upper lip swelling with primary reconstruction of lip defect and supraomohyoid neck dissection.Diagnosis of myoepithelial carcinoma could only be made by histopathological examination of the resected specimen. Myoepithelial differentiation of tumor cells was established by showing positivity for CK7 and SMA. To the best of our knowledge, this is the first case of myoepithelial carcinoma arising in a recurrent pleomorphic adenoma in the upper lip.